Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Kreativitasbelajar Siswa Kelas VII C Pada Mata Pelajaran IPS Di SMP Al-Islam 1 Surakarta Tahun Ajaran 2016/2017 - Octavia.W., Fajar, Dr.Suyatmini,SE.,M.Si (2017)
This study was aimed to improve the learning activity by applying of scientific approach with learning model of problem-based learning (pbl)methodfor students of class VII C SMP Al - Islam 1 Surakarta in 2016/2017 academic year. This study was a classroom action research which was conducted in two cycles. The subjects in this study were teachers who provide action and the action recipients were students of class VII C of SMP AL Islam I Surakarta with total 25 students. The method of collecting data which used in this study were interviews, observation, field notes, and documentation. The techniques of data analysis used in this study were data reduction, data presentation, and data verification. The results of this research showed an increase creativity of student learning that can be seen from the indicators, namely : 1) Have a great curiosity of prior before action was 6 students (24%) and at the end of the actionit became 21 students (84%), 2) often ask good questions before the measure as many as 4 students (16%) and at the end of the action as many as 23 students (92%),3) provide many ideas and proposal into a problem before action was 5 students (20%), and at the end of the action as many as 19 students (76%), 4) able to express idea spontaneously and daringbefore action was 5 students (20%) and at the end of the actionit became 20 students(80%).Based on the description above can be concluded that the application of problem based learning method can enhance students' learning creativity on social science subject for students of class VII C SMP Al Islam 1 Surakarta on social science subject 2016/2017 academic year